A Detailed Step-by-Step Description of the Measurement of Absolute Inductances of Permanent Magnet Synchronous Machines - Kellner, Sven; Piepenbreier, Bernhard (International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, 2012)
This paper presents a detailed description of the measurement process of the absolute in ductances L,i and Lq of permanent magnet synchronous machines (PMSMs). Knowledge of the inductances of the PMSMs is very important for closed loop control of the machine. The measurement is based on the well known linearized PMSM equations [1]. Both the theoretical background of the inductance measurement such as the influences of iron losses [2,3,4.5] and the actual realization of the measurement process itself are discussed in the paper. While the test bench setup can prepared quickly and easily, the calculation of the inductances based on the measurement results is fairly complex. The paper shows the whole measurement process in detail. © VDE Verlag GMBH - Berlin.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.adetai

Advantages of a new approach for estimating the stator resistance of a permanent magnet synchronous machine compared to known conventional methods - Kellner, Sven; Piepenbreier, Bernhard (Vehicle Power and Propulsion Conference, 2010)
Usually, electrical propulsion vehicles are driven by highly dynamic drive controls. To make this possible, it is important to know electrical parameters such as inductances, flux and stator resistance as exactly as possible. In particular, the ohmic stator resistance Rs changes during operation due to temperature changes. Therefore, it is not possible to achieve a high precision over a wide operating temperature range with an offline measurement of Rs. In this paper, a new identification method for stator resistance is presented and compared to a known method. While the conventional method only works properly at certain operating points, the new method does not have this limitation. © Copyright 2011 IEEE - All Rights Reserved.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.advant
Keywords: Adjustable speed drive; Control of drive; Drive; Electrical drive; Electrical machine; Permanent magnet motor; Variable speed drive

A multiple model approach to fault detection and localization in multi-terminal HVDC systems - Al Hage Ali, Ali; Piepenbreier, Bernhard; Buchstaller, Dominic; Engel, Markus (41st Annual Conference of the IEEE Industrial Electronics Society, IECON 2015, 2016)
This paper discusses a novel protection technique for DC line faults in multi-terminal HVDC (MTDC) systems. Hereby a bank of Kalman filters ranks the fit of a discrete set of line fault models to measured data. The best fitting model indicates the fault location and fault type. The suitability of the technique is discussed for fast on-line fault localization and exact off-line fault localization and fault identification. Experimental results are shown to validate the approach based on data from a high fidelity simulation of a 3-terminal HVDC system.
Keywords: DC; fault detection; fault localization; HVDC; Kalman filter; Multi-terminal; multiple model; protection

Analysis and Modelling of Common-Mode Oscillations of Electrical Drive Systems with Active Front End and Long Motor Cables - Weidinger, Thomas; Piepenbreier, Bernhard (SPEEDAM 2008, 2008)
This paper presents an analysis of common-mode oscillations in electrical drive systems. The analysed oscillations occur particularly in electrical drive systems with active front end, common DC-link and long shielded motor cables. Because of resonant frequencies at 10 to 40 kHz low damping occurs. In the concerned frequency range switching operations generate a significant excitation. As the focus of this paper the common mode system of an electrical drive system is analysed and modelled. The damping behaviour of the choke and the switching of active front end and inverters have to be analysed very carefully. Simulations and measurements show apparent voltage stressing of motors, common mode losses and currents that disturb the drive system. ©2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEEAS.analys
Keywords: Common-mode noise; EMC; EMI; Modelling

Analysis of GaN HEMT switching behavior - Lautner, Jennifer; Piepenbreier, Bernhard (ICPE-ECCE Asia, 2015)
This paper presents a comprehensive study of the GaN HEMT switching performance in a phase-leg configuration with special focus on the impact of different parasitic effects. Therefore, a simulation model of a double pulse test circuit with GaN devices and including parasitic elements is proposed. The causes of parasitic inductances and capacitances are discussed and their effects are analyzed. Furthermore, the influence of the gate resistance value and dead time is investigated. A double pulse tester was designed to experimentally verify the simulation results. This paper shows the switching transients of both devices in a phase-leg configuration for varying parameters graphically and offers a better insight into the switching behavior of GaN transistors. The understanding of the parasitic effects and varying parameter enables improved design and performance of fast switching power converters.
UnivIS-Import:2017-11-06:Pub.2015.tech.IE.LEEAS.analys_6
Keywords: dead time; GaN HEMT; parasitics; phase-leg; switching performance

A Novel Scheme for Single-Phase AC-DC Power Conversion with Unity Power Factor and Regenerative Feedback - Völkel, Stefan; Piepenbreier, Bernhard (PCIM Europe 2006, 2006)
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEEAS.anovel

A Practical Analysis of SiC-JFETs for a Power Converter Application - Orellana Raccoursier, Alvaro Marcelo; Piepenbreier, Bernhard (PCIM Europe 2006, 2006)
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.LEEAS.apract

Auswertung magnetischer Eigenschaften von Permanentmagneterregten Synchronmaschinen zur geberlosen Regelung, Innovative Klein- und Mikroantriebstechnik - Reill, Josef; Piepenbreier, Bernhard; Hahn, Ingo (ETG/GMM, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.auswer

Bandwidth Extending Approach for Sensorless Control of Synchronous Reluctance Machines Using an HF Square-Wave-Shaped-Voltage-Injection-Based Method for Low Speed Range - Bugsch, Martha; Piepenbreier, Bernhard (2018 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2018, 2018)
Keywords: Alternating square-wave-shaped voltage injection; 2DoF; Sensorless control; HF test voltage injection; Synchronous reluctance machines

Bi-directional AC-AC Z-Source Inverter with active Rectifier and Feedforward Control - von Zimmermann, Moritz; Labusch, Sebastian; Piepenbreier, Bernhard (IEEE Energy Conversion Congress and Exposition, 2010)
Z-Source inverters, consisting of both inductors and capacitors as DC link components, provide unique boost capability in contrast to conventional inverters. The simple structure needs no additional switching elements and only small step-up chokes. Due to the oscillatory arrangement of both inductors and capacitors in the DC link, voltages and currents exhibit characteristical dynamic behavior especially when using the Z-source inverter with an AC supply. The consequences are distortion of the output voltage and self-boosting due to unwanted shoot-through states and oscillating DC link voltage due to mains voltage rectifying. An active front end topology in combination with a damped filter is proposed to prevent any unwanted shoot-through states. Besides, regenerating operation of the Z-source inverter with AC supply is enabled. Resting on this new structure with minimized passive components, a state space description is given. Subsequently, a feedforward control is designed to avoid load current harmonics caused by mains voltage rectifying. Experimental results verify the suitability. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.bidire
Keywords: AC-AC converter; Dynamic analysis; Feedforward controller; Small-signal modeling; Variable speed drives; Voltage control; Z-source inverter

Carrier signal based sensorless control of electrically excited synchronous machines at standstill and low speed using the rotor winding as a receiver - Rambetius, Alexander; Ebersberger, Sebastian; Seilmeier, Markus; Piepenbreier, Bernhard (Power Electronics and Applications (EPE), 2013 15th European Conference, 2013)
This paper presents a new carrier signal based approach for motion sensorless control of electrically excited synchronous machines. In the case of permanent magnet synchronous machines sensorless control at standstill and low speed is mostly done by injecting a high-frequency voltage and evaluating the resulting current response. Hence, the stator is used as the transmitter and as the receiver of the carrier signal. The major drawback is that a magnetic saliency is mandatory. In the case of electrically excited synchronous machines the rotor voltage serves as an additional input to the system and the resulting field current as an additional, easy to measure, state variable. The presented approach makes use of this fact and uses the field winding as the receiver of a carrier signal, which is injected into the stator winding. Like this no magnetic saliency is mandatory in order to track the position. The new approach is compared to a well-known carrier signal based method, in which the stator works as the transmitter and as the receiver of the carrier signal. In this case a magnetic saliency is mandatory which differs from the saliency necessary for permanent magnet synchronous machines. The applicability of both approaches is proven in experiments. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.carrie
Keywords: Sensorless control; Synchronous motor; Traction application; Vector control

Carrier Signal Based Sensorless Control of Wound Field Synchronous Machines Using the Rotor Winding as the Receiver: Rotating vs. Alternating Carrier Signal - Piepenbreier, Bernhard; Rambetius, Alexander (PCIM, 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.IE.LEEAS.carrie

Comparing Switching Performance of Gallium Nitride HEMT and Silicon Power MOSFET - Lautner, Jennifer; Piepenbreier, Bernhard (Proceedings of PCIM Europe 2015, 2015)
UnivIS-Import:2017-11-06:Pub.2015.tech.IE.LEEAS.compar

Comparison of carrier signal based approaches for sensorless wound rotor synchronous machines - Piepenbreier, Bernhard; Rambetius, Alexander (2014 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM 2014), 2014)
Wound rotor synchronous machines enable a large variety of approaches for carrier signal based sensorless control since the rotor voltage serves as an additional input to the system and the rotor current as an additional, easy to measure, state variable. Consequently it is possible to use the rotor winding either as the transmitter or as the receiver of a carrier signal. In these cases the mutual inductance between the d-axis and the rotor winding is of major importance. Moreover a rotor saliency can be evaluated if the stator is used as the transmitter and as the receiver of the carrier signal. If voltage injection is used, the rotor winding acts like a damper winding for the carrier signal and consequently the evaluated saliency differs from the saliency which is utilized for sensorless control of permanent magnet synchronous machines. Carrier current control on the other hand offers the possibility to evaluate a magnetic saliency regarding the inductances in the d-and q-axis. This work provides a detailed review of the aforementioned approaches and analyses the prerequisites. In addition to this the different approaches are made comparable in terms of signal-to-noise ratio and cross saturation. This is done by introducing suitable intensity terms. With the help of identified parameters the most promising approach for the investigated machine is found. Experimental results confirm the validity of the comparison. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.compar_2
Keywords: electrically excited synchronous machine; high frequency injection; sensorless control; traction motor; wound field synchronous machine; wound rotor synchronous machine

Comparison of Model-based Sensorless Control Methods for a PM-assisted Synchronous Reluctance Machine with a Ribless Rotor - Zimmermann, Marco; Simson, Werner; Piepenbreier, Bernhard (2019 IEEE 28th International Symposium on Industrial Electronics (ISIE), 2019)
Keywords: sensorless control; self-sensing; permanent magnet assisted; synchronous reluctance machine; model-based

Compensation of PWM Inverter Voltage Errors based on Measurement of DC-Link and Output Voltages - Beer, Eva Katharina; Kellner, Sven; Piepenbreier, Bernhard (International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.compen

Design of a permanent magnet assisted synchronous reluctance machine enhanced for saliency based sensorless control - Zimmermann, Marco; Piepenbreier, Bernhard (2017 IEEE International Electric Machines and Drives Conference (IEMDC), 2017)

Determination of Differential Inductances for a Permanent Magnet assisted Synchronous Reluctance Machine with a Ribless Rotor - Zimmermann, Marco; Piepenbreier, Bernhard (2018 IEEE Transportation Electrification Conference and Expo (ITEC), 2018)
Keywords: Rotors; Couplings; Harmonic analysis; Inductance; Windings; Saturation; Reluctance machines

Dimensioning of the Z-Source Inverter for General Purpose Drives with Three-Phase Standard Motors - Sack, Lothar; von Zimmermann, Moritz; Piepenbreier, Bernhard (IEEE PESC 08, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEEAS.dimens

Experimental Results and Parameter Identification of a Permanent Magnet assisted Synchronous Reluctance Machine with a Ribless Rotor - Zimmermann, Marco; Lange, Alexander; Piepenbreier, Bernhard (2018 IEEE International Magnetic Conference (INTERMAG), 2018)
Keywords: Ferrite assisted; Paramenter Identification; Sensorless Control; Synchronous Reluctance Machine

Fast Gate Drive for SiC-JFET using a Conventional Driver for MOSFETs and Additional Protections - Piepenbreier, Bernhard; et al. (The 30th Annual Conference of the IEEE Industrial Electronics Society, 2004)
A new gate drive for SiC-JFET (Silicon Carbide Junction Field Effect Transistor) is developed and tested on a half-bridge. For the realization of a fast gate drive which offers full protection for the SiC-JFET, a gate drive concept is firstly chosen. The gate drive unit has an output stage made for MOSFETs, a new kind of fast signal isolator, short circuit protection and overvoltage protection. © 2004 IEEE.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEEAS.fastga

Flatness Based Sensorless Control of PMSM Using Test Current Signal Injection and Compensation for Differential Cross-Coupling Inductances at Standstill and Low Speed Range - Piepenbreier, Bernhard; Seilmeier, Markus; et al. (IEEE International Symposium on Sensorless Control for Electrical Drives and Predictive Control of Electrical Drives & Power Electronics (SLED-PRECEDE 2013), 2013)
This paper presents a novel flatness based two-degree-of-freedom (2DoF) sensorless control scheme for PMSM at standstill and for low speed range using test current signal injection in the estimated d-axis of the field oriented dq-coordinate system. Asymmetrical winding and saturation might cause the occurrence of differential cross-coupling inductances and as a result the estimated rotor position deviates from the real value. The differential cross-coupling inductances have to be compensated for to overcome this problem. For that a flatness based dynamic feed-forward control is proposed. The control error due to model uncertainties is minimized using a controller that fulfills the internal model principle. The control signal of the high frequency controller in the q-axis is demodulated and afterwards used as the input signal of a tracking-observer to estimate the rotor position. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.flatne
Keywords: Inductances; Permanent magnet machines; Sensorless control; State-space methods

Flatness Based Sensorless Control of PMSM Using Test Current Signal Injection and Compensation for Differential Cross-Coupling Inductances at Standstill and Low Speed Range - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (2013)
This paper presents a novel flatness based two-degree-of-freedom (2DoF) sensorless control scheme for PMSM at standstill and for low speed range using test current signal injection in the estimated d-axis of the field oriented dq-coordinate system. Asymmetrical winding and saturation might cause the occurrence of differential cross-coupling inductances and as a result the estimated rotor position deviates from the real value. The differential cross-coupling inductances have to be compensated for to overcome this problem. For that a flatness based dynamic feed-forward control is proposed. The control error due to model uncertainties is minimized using a controller that fulfills the internal model principle. The control signal of the high frequency controller in the q-axis is demodulated and afterwards used as the input signal of a tracking-observer to estimate the rotor position.
Keywords: Sensorless control; Permanent magnet machines; State-space methods; Inductances

Fundamental-Frequency-Front-End-Umrichter - ein rückspeisefähiger Antriebsumrichter ohne Elektrolytkondensatoren im Zwischenkreis - Piepenbreier, Bernhard (VDMA Technik im Dialog: Mechatronik, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEEAS.fundam_6

General PMSM d,q-Model Using Optimized Interpolated Absolute and Differential Inductance Surfaces - Piepenbreier, Bernhard; et al. (International Electric Machines and Drives Conference 2011 (IEMDC 2011), 2011)
Widely used permanent magnet synchronous machines (PMSMs) often show a significant inductance variation near and above the rated current values due to saturation. When the inductances are no longer constant, the model equations have to be modified. This paper proposes new, extended equations, which are as similar as possible to the linearized equations, to make the conversion of existing control schemes to the new approach as easy as possible. In addition, methods to measure the inductances needed for the new PMSM equations are explained together with an efficient implementation of the inductances. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.genera

Großserientaugliche Nadelwickeltechnik für verteilte Wicklungen im Anwendungsfall der E-Traktionsantriebe: Der Technischen Fakultät der Friedrich-Alexander-Universität Erlangen-Nürnberg zur Erlangung des Doktorgrades Dr.-Ingenieur - Stenzel, Peer; Franke, Jörg; Piepenbreier, Bernhard; Endisch, Christian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2017)
Einleitung Innerhalb seiner nunmehr über einhundertjährigen Geschichte hat sich das Automobil zum beliebtesten Individualtransportmittel entwickelt [1]. Dabei konnte sich der Verbrennungsmotor auf Basis fossiler Kraftstoffe gegenüber anderen Antriebsarten durchsetzen [2]. Trotz vieler verbrauchssenkender Innovationen in der sogenannten konventionellen Antriebstechnik nehmen die verkehrsbedingten CO2-Emissionen aufgrund des weltweit steigenden Verkehrsaufkommens weiterhin zu [3, 4]. In den Jahren von 2000 bis 2010 betrug die Zunahme der straßenverkehrsbe-dingten CO2-Emissionen 14 % [3], während im gleichen Zeitraum der weltweite KFZ-Bestand um 33 % auf mehr als eine Mrd. Fahrzeuge anstieg [5]. Um den CO2-Ausstoß einzudämmen, hat die Europäische Kommission daher ein gesetzliches Limit in Höhe von 95 g CO2 / km für den Durchschnittsflottenverbrauch aller in der EU neu zugelassenen PKWs beschlossen, das stufenweise in Kraft tritt [6]. Die Emissionen werden über den Neuen Europäischen Fahrzyklus (NEFZ) ermittelt. Bei Nichteinhaltung drohen empfindliche Strafen [1]. Auch andere Länder, wie die USA, Japan und China haben Verbrauchs-, bzw. Emissionsvorschriften. Diese Vorschriften stellen insbesondere die Premiumhersteller, wie beispielsweise Audi, BMW und Daimler, vor große Herausforderungen, da deren Kunden vorzugsweise leistungsstärkere Modelle kaufen, die einen höheren Kraftstoffverbrauch zur Folge haben. Aus diesem Grund gibt es bei den Automobilherstellern Bestrebungen, den Verbrennungsmotor teilweise oder vollständig durch den Elektromotor zu substituieren. Für die Kundenakzeptanz ist dabei entscheidend, dass die Hybrid- (HEV) und Elektrofahrzeuge (BEV) im Vergleich zum konventionell angetriebenen Fahrzeug vergleichbare Preise, ausreichende Reichweiten und möglichst weiteren exklusiven Zusatznutzen, wie besseres Beschleunigungsverhalten oder geringere Wartungszyklen aufweisen. Daraus ergeben sich für die für den Antrieb infrage kommenden Drehstrommaschinen unter anderem die Forderungen nach einer hohen Leistungsdichte und einem hohen Wirkungsgrad über ein breites Drehmoment-Drehzahl-Band sowie nach einer wirtschaftlichen Herstellbarkeit. Während die elektromagnetische Auslegung der E-Maschine Gegenstand von vielen Untersu-chungen und Veröffentlichungen ist, wurde in der Vergangenheit der Fertigung von Elektromaschinen hingegen in Literatur und Forschung nur wenig Beachtung geschenkt. Dabei liegt ein wesentliches Entwicklungspotenzial in der Fertigung, da die Herstellungstechnologien, und insbesondere die Wickeltechnologie des Stators, einerseits die Herstellungskosten bestimmen und andererseits die elektromagne-tische Auslegung und die Konstruktion des Elektromotors einschränken. Dies geschieht in Form von erreichbaren Kupferfüllfaktoren, umsetzbaren Wickelschemata und Bauraumforderungen durch die Wickelkopfhöhe. Während die konzentrierte Wicklung als eine der zwei Ausprägungsformen der Drehstromwicklungen gut industrialisiert ist und viele Automatisierungsmöglichkeiten bietet [7], existieren für 1 Einleitung 2 die andere Wicklungsart, die sogenannte verteilte Wicklung, nur wenige wickeltechnische Möglichkeiten, die großserientauglich sind und gute Produkteigen-schaften ermöglichen. Dies ist insofern nachteilig, da die verteilte Wicklung ein wesentlich breiteres Anwendungsspektrum hat und sich die konzentrierte Wicklung, wie in Kapitel 2 gezeigt wird, für Asynchronmaschinen und Achsantriebe in Elektro-Fahrzeugen nicht gut eignet. Im Falle von verteilten Runddrahtwicklungen wird üblicherweise die Einziehtechnik verwendet, die zwar seit mehreren Jahrzehnten etabliert [8], jedoch aufgrund vieler manueller Tätigkeiten nur bedingt großserien-tauglich ist. Darüber hinaus sind mit der Einziehtechnologie durch die prinzipbedingte Wildwicklung nur mittlere Kupferfüllfaktoren erzielbar. Eine Alternative bietet die Nadelwickeltechnik, die Potenzial bezüglich Kupferfüllfaktor und Automatisierbarkeit aufweist, bisher für verteilte Wicklungen jedoch nur bei Industrieantrieben zur Anwendung kam, welche geringere Anforderungen an Wickelkopfhöhe und Kupferfüllfaktor stellen. Vor diesem Hintergrund ergibt sich die Aufgabenstellung dieser Arbeit, die Nadelwickeltechnik für verteilte Wicklungen von Traktionsantrieben weiter-zuentwickeln und auf die automobilen Bedürfnisse anzupassen. Dies bedeutet, dass der Wickelprozess samt nachgelagerten Prozessschritten möglichst vollständig automatisierbar und damit großserientauglich werden soll. Darüber hinaus sind die Produkteigenschaften der E-Traktionsmaschine zu optimieren. Zunächst werden in Kapitel 2 die Grundlagen elektrischer Drehstrommaschinen sowie deren Aufbau beschrieben. Anschließend werden die zwei Ausprägungen der Drehstromwicklungen - die konzentrierte und die verteilte Wicklung - erläutert. In Kapitel 3 erfolgt die Beschreibung alternativer Herstellverfahren für verteilte Wicklungen sowie die Erläuterung des Zusammenhangs zwischen Produkteigen-schaften und Fertigung. Darauf aufbauend werden die Entwicklungs- und Optimierungsziele für das Nadelwickelverfahren abgeleitet. Neben dem allgemeinen Automatisierungsziel werden die Wickelkopfhöhe und der Kupferfüllfaktor, bzw. der Wicklungswiderstand als wesentliche Produktbeeinflussungsmöglichkeiten und damit Optimierungsziele identifiziert. Darüber hinaus wird aus den Ergebnissen bezüglich des Zusammenhangs zwischen Produkteigenschaften und Wickelverfahren der Drahtzugkraft eine besondere Bedeutung für den Wicklungswiderstand bei-gemessen, was überprüft werden soll. Zudem wird festgelegt, dass für die weiteren Entwicklungen und Untersuchungen eine Asynchronmaschine aus einem aktuellen Fahrzeugprojekt verwendet wird. Mithilfe von experimentellen Wickelversuchen an einer Parallelkinematik werden in Kapitel 4 der Einfluss der Drahtzugkraft auf den Wicklungswiderstand sowie der Einfluss der Nadelgeometrie auf die Drahtzugkraft untersucht. In Kapitel 5 erfolgt die Konzeptentwicklung zur Erhöhung des Füllfaktors unter Nutzung der Nadelwickeltechnik. Dabei wird ein Lösungsansatz erarbeitet und 1 Einleitung 3 prototypisch an einer Parallelkinematik erprobt. Die Grundidee besteht darin, mithilfe einer gebogenen Wickelnadel die schwer zugänglichen Bereiche der Nut zu erreichen und den Draht unmittelbar an der gewünschten Position zu platzieren, um so eine lagegenaue Wicklung zu erreichen. Da der Ansatz für die Implementierung in eine industrielle Nadelwickelanlage, unter anderem aufgrund des Bauraumbedarfs und der zusätzlichen Masse durch den Servoantrieb, herausfordernd ist, wird auf Basis der Versuchsergebnisse ein zweiter Ansatz mit einem kinematisch optimierten Prinzip entwickelt. In Kapitel 6 wird ein Ansatz zur Optimierung des Wickelkopfes beschrieben. Ausgehend von einigen grundsätzlichen überlegungen zur Wickelkopfoptimierung werden mehrere Lösungsansätze erarbeitet und bewertet. Der Ansatz eines temporär gefügten Wickelwerkzeugs zeigt dabei das größte Potenzial und wird daraufhin konstruktiv umgesetzt. Aufgrund der hohen wirkenden Wickelkräfte wird ein FE-Modell des Werkzeugs entwickelt und validiert. Die Wickelkräfte als Eingangsparameter für das FE-Modell werden im Versuch experimentell ermittelt. Anschließend wird zum Nachweis der Prinziptauglichkeit mithilfe der weiter-entwickelten Nadelwickelmethode eine E-Maschine prototypisch aufgebaut. In Kapitel 7 werden die Produkteigenschaften des nadelgewickelten Prototyps über Prüfstandmessungen ermittelt und mit denen einer Referenzmaschine verglichen, um die Nadelwickeltechnologie hinsichtlich ihrer Auswirkungen auf das Betriebsver-halten zu untersuchen. Den Abschluss der Arbeit bildet eine Wirtschaftlichkeitsunter-suchung in Kapitel 8, bei der das weiterentwickelte Nadelwickelverfahren mit der Einziehtechnik verglichen wird.
Keywords: Anlagenplanung; Assembling; assembly; assembly machines; Coil winding; E|DRIVE; E|DRIVE; Automated Winding Assembly; Stator; Key Words: Robot-based; E|DRIVE; Automated Winding Assembly; Stator; Robot- based; Cover; E|DRIVE; electromagnetic actuators; magnetic stray fields; nondestructive measurement system; GMR-sensor; E|DRIVE; Elektromaschinenbau; Füllfaktor; Effizienz; Mechatronics; production; Production engineering; Produktion; system integration; Technology; winding of HF-litz wires; Wires

Harmonic Diversity and Determining Factors of Radial Forces in External Rotor Permanent Magnet Synchronous Motors with Concentrated Windings - Krotsch, Jens; Piepenbreier, Bernhard (ICEM, 2010)
In external rotor permanent magnet synchronous motors, also the higher frequency harmonics of the radial forces generate considerable resonant vibrations and acoustic noise. Therefore, diversity of spatial and especially frequency harmonic ordinal numbers of representative slot and pole number combinations are derived analytically with open-circuit and under load. Amplitudes of radial force waves are calculated by means of the finite element method and two-dimensional Fourier analysis. The obtained results confirm the analytical investigation. Determining factors on amplitudes are analyzed on a machine having 12 slots, 10 poles and a double-layer winding. Higher frequency harmonics can be significantly affected by pole and tooth shaping. With open-circuit, the calculations are validated by experimental results. ©2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.harmon
Keywords: Concentrated windings; External rotor; Finite element analysis; Ordinal numbers; Permanent magnet synchronous motor; Radial force waves; Resonant vibrations

Harmonic Optimization for Multilevel Converters Using Space Vector Fundamental Frequency Modulation - Mehlmann, Gert; von Zimmermann, Moritz; Piepenbreier, Bernhard; Herold, Gerhard (EPE-ECCE 2011 - Birmingham, 2011)
Multilevel converters feature a staircase output voltage, resulting in a lower number of switching operations and better spectral characteristics. Switching every element only once a load cycle (fundamental frequency switching), losses can be minimized. By calculating optimum switching angles, the emergence of lower harmonics can be avoided. Derived from conventional space vector modulation (SVPWM), a novel method overcoming the complexity of selective harmonic elimination (SHE) is presented. It optimizes the spectrum while being suitable for real-time calculation. A simple and easy to implement routing algorithm to choose appropriate switching states is given, which works for an arbitrary number of levels. Finally, results from both space vector fundamental frequency modulation (SVFFM) and selective harmonic elimination are compared. © 2011 EPE Association - European Power Electr.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS._harmo
Keywords: Harmonics; Modulation strategy; Multilevel converters

HF parameter identification using test current injection for sensorless control of a synchronous reluctance machine (SynRM) - Bugsch, Martha; Piepenbreier, Bernhard (18th European Conference on Power Electronics and Applications, EPE 2016 ECCE Europe, 2016)
An increasing number of sensorless control methods are being developed for a recently rediscovered machine type: synchronous reluctance machines (SynRMs). The advantage of sensorless control methods is that the position sensor can be omitted. Many alternative methods are conceivable, but in all of them, it is impossible to observe and estimate the electrical rotor position at standstill and at low speed without additional excitation via high-frequency (HF) test signals. To calculate the position information from the current or voltage response of these test signals, a detailed machine model is necessary. The challenge is to identify the parameter of the machine model that characterises the HF machine behaviour. Thus, there is a need to find a proper identification method and to analyse these HF parameters for different HF test signal frequencies and amplitudes. Thereby, one can determine which test signal frequencies and amplitudes are best suited for sensorless control of SynRMs. Therefore in this paper an HF parameter identification method is described and the corresponding measurement results for a SynRM are analysed. A test current signal injection method is used. Different test signal frequencies and amplitudes, as well as the position dependencies, are compared. It can be concluded that, first a appropriate test signal frequency and amplitude combination has to be selected that offers enough voltage reserve to control the fundamental behaviour of the machine. Moreover, the HF parameters should be measured exactly for the combination used because there is a dependency of the HF parameters on the test signal frequency and amplitude that is significant but not equally strong. Position averaged measured values ensure high-precision HF parameter results. SynRMs are suitable for saliency-based sensorless control methods based on test signal injection because they have an inherent machine parameter saliency due to their rotor design.
Keywords: Synchronous motor; Sensorless control; Self-sensing control; Reluctance drive

HF Test Current Injection Based Self-Sensing Control of PMSM for Low and Zero Speed Range Using Two-Degree-of-Freedom Current Control. - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (IEEE International Symposium on Sensorless Control for Electrical Drives (SLED 2014), 2014)
This paper deals with an innovative self-sensing control scheme based on test current instead of voltage injection. Using Two-Degree-of-Freedom current control one can overcome the bandwidth limitations which made test current injection unattractive during the last 20 years. The Two-Degree-of-Freedom control scheme consists of a model based dynamic feed forward control to set the reference response and model reference tracking controllers providing disturbance rejection and the position error signals for self-sensing control. Since Two-Degree-of-Freedom control is a model based control scheme the compensation for secondary saliencies is inherently included in the pre-control. It is shown analytically that in case of test current instead of voltage injection just the precise knowledge of the current and position dependent inductance mqd HF is needed in case of inductance saliency based sensorless control. The effectiveness of the proposed method is proven by experimental results. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.hftest
Keywords: permanent magnet motors; saliency; sensorless control; test current injection

HF Test Current Injection Based Self-Sensing Control of PMSM for Low and Zero Speed Range using Two-Degree-of-Freedom Current Control - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (2014)
This paper deals with an innovative self-sensing control scheme based on test current instead of voltage injection. Using Two-Degree-of-Freedom current control one can overcome the bandwidth limitations which made test current injection unattractive during the last 20 years. The Two-Degree-of-Freedom control scheme consists of a model based dynamic feed forward control to set the reference response and model reference tracking controllers providing disturbance rejection and the position error signals for self-sensing control. Since Two-Degree-of-Freedom control is a model based control scheme the compensation for secondary saliencies is inherently included in the pre-control. It is shown analytically that in case of test current instead of voltage injection just the precise knowledge of the current and position dependent inductance m(qd)(HF) is needed in case of inductance saliency based sensorless control. The effectiveness of the proposed method is proven by experimental results.
Keywords: permanent magnet motors; sensorless control; saliency; test current injection

HF Test Current Injection-Based Self-Sensing Control of PMSM for Low- and Zero-Speed Range Using Two-Degree-of-Freedom Current Control - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (IEEE Transactions on Industry Applications, 2015)
This paper deals with an innovative self-sensing control scheme based on test current instead of voltage injection. Using two-degree-of-freedom current control, one can overcome the bandwidth limitations that made test current injection unattractive during the last 20 years. The two-degree-of-freedom control scheme consists of a model-based dynamic feedforward control to set the reference response and model reference tracking controllers providing disturbance rejection and position error signals for self-sensing control. Since two-degree-of-freedom control is a model-based control scheme, the compensation for secondary saliencies is inherently included in the precontrol. It is analytically shown that, in the case of alternating test current instead of voltage injection, just the precise knowledge, in general, of the current- and position-dependent secondary diagonal element of the inductance matrix is needed in the case of inductance saliency-based self-sensing control. The effectiveness of the proposed method is proven by experimental results.
UnivIS-Import:2015-07-08:Pub.2015.tech.IE.LEEAS.hftest
Keywords: Current control; eddy currents; machine vector control; magnetic losses; motion control; permanent-magnet machines; permanent-magnet motors; saliency; self-sensing control; sensorless control; test current injection

HF Test Current Injection-Based Self-Sensing Control of PMSM for Low- and Zero-Speed Range Using Two-Degree-of-Freedom Current Control - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (IEEE Transactions on Industry Applications, 2015)
This paper deals with an innovative self-sensing control scheme based on test current instead of voltage injection. Using two-degree-of-freedom current control, one can overcome the bandwidth limitations that made test current injection unattractive during the last 20 years. The two-degree-of-freedom control scheme consists of a model-based dynamic feedforward control to set the reference response and model reference tracking controllers providing disturbance rejection and position error signals for self-sensing control. Since two-degree-of-freedom control is a model-based control scheme, the compensation for secondary saliencies is inherently included in the precontrol. It is analytically shown that, in the case of alternating test current instead of voltage injection, just the precise knowledge, in general, of the current- and position-dependent secondary diagonal element of the inductance matrix is needed in the case of inductance saliency-based self-sensing control. The effectiveness of the proposed method is proven by experimental results.
Keywords: Current control; eddy currents; machine vector control; magnetic losses; motion control; permanent-magnet machines; permanent-magnet motors; saliency; self-sensing control; sensorless control; test current injection

HF Test Current-Ripple-Control-Based Sensorless Method for SynRMs in the Low- and Zero-Speed Range Leading to an Adaptive Square-Wave-Shaped Voltage Injection - Bugsch, Martha; Piepenbreier, Bernhard (2018 IEEE 9th International Symposium on Sensorless Control for Electrical Drives (SLED), 2018)
Keywords: Sensorless control; Self-sensing control; Synchronous reluctance machines; 2DoF; alternating HF test current injection; HF test current control

High-Bandwidth Sensorless Control of Synchronous Reluctance Machines in the Low- And Zero-Speed Range - Bugsch, Martha; Piepenbreier, Bernhard (IEEE Transactions on Industry Applications, 2020)
Two aspects of sensorless control of synchronous reluctance machines (SynRMs) in the low-speed and zero-speed range are gaining more and more importance: how to achieve a high control bandwidth and how to lower the test current amplitude to minimize audible noise and high-frequency (HF) losses. A high control bandwidth can be realized by a square-wave-shaped voltage injection (SWSVI). This article presents a new approach, controlling the current ripple generated by the SWSVI constant and simultaneously maintaining a minimum required HF test current amplitude. The proposed solution is optimized for the highly nonlinear machine behavior of SynRMs combined with a standard industrial inverter using regular current sampling. A new low-noise current demodulation by a Kalman filter and its empiric tuning is presented. The prediction step of the filter compensates for the dead time of the control algorithm. Experimental results confirm the excellent performance. Compared to the conventional binomial filter, only half of the test signal amplitude is required. The mean square error of the current demodulation was reduced by 90%.
CRIS-Team Scopus Importer:2020-05-12
Keywords: Alternating square-wave-shaped voltage injection (SWSVI); high-frequency (HF) test current control; Kalman filter (KF); observer; self-sensing control; sensorless control; synchronous reluctance machine (SynRM)

High Efficiency Three-Level Simplified Neutral Point Clamped (3L-SNPC) Inverter with GaN-Si Hybrid Structure - Lange, Alexander; Lautner, Jennifer; Piepenbreier, Bernhard (PCIM Europe 2018; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, 2018)

High Efficiency Three-Phase-Inverter with 650 V GaN HEMTs - Lautner, Jennifer; Piepenbreier, Bernhard (PCIM Europe 2016, 2016)
UnivIS-Import:2017-11-06:Pub.2016.tech.IE.LEEAS.highef

High Precision Identification Method for differential dq-Inductances of Permanent Magnet Synchronous Machines - Reill, Josef; Kellner, Sven; Ebersberger, Sebastian; Seilmeier, Markus; Piepenbreier, Bernhard (International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.highpr

High Precision Identification Method for differential dq-lnductances of Permanent Magnet Synchronous Machines - Seilmeier, Markus; Ebersberger, Sebastian; Kellner, Sven; Piepenbreier, Bernhard; Reill, Josef (2010)
This paper presents a novel method to measure the dq-inductances of permanent magnet synchronous motors (PSM). Accurate knowledge of the machine parameters is very important for high precision field oriented control of PSMs. Additionally there is a trend towards sensorless control of this type of machine. Especially sensorless control with test signals is based on the differential inductances. However, the parameters vary during operation. On the one hand the inductances and the permanent magnet flux mainly depend on the load of the machine. On the other hand the stator resistance changes with temperature. As there actually exist methods to get the absolute dq-inductances this topic is kept short. The focus in this publication is set to the differential inductances.The authors propose a high frequency signal based method to analyse the load and frequency dependent differential inductances in the rotor reference frame with very high precision. The method was tested in the laboratory with different machines and brought reliable results.

High Voltage IGBTs and Medium Frequency Transformer in DC-DC Converters for Railway Applications - Hoffmann, Holger; Piepenbreier, Bernhard (SPEEDAM 2010, 2010)
A converter system made of series-connected converter submodules based on medium frequency (MF)-dc/dc converters can replace the conventional traction transformer that works at frequencies of 16.7 Hz or 50 Hz saving both mass and energy. Engaging multilevel topology permits the connection to the HV catenary with a line choke. MF switching performance of typical and dedicated 6.5 kV IGBTs was characterized and is given herein. The impact of chosen switching frequency and resonance frequency on transformer mass and transformer efficiency was analyzed with a coupled electromagnetic, thermal and hydraulic transformer calculation. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.highvo
Keywords: High voltage power converters; IGBT; Medium frequency transformer; Multilevel converter; Rail vehicle; Resonant converter

Hybrid Algorithm for Multi-objective Optimization of PMSM using massively distributed Finite Element Analysis - Krotsch, Jens; Piepenbreier, Bernhard (Optimization of Electrical and Electronic Equipment, 2010)
A hybrid multi-objective optimization algorithm based on partial aspects of evolution strategy combining stochastic and deterministic elements with the aim of a high efficiency and high scalability suitable for massively distributed finite element analysis is investigated. The selection and generation process of solution candidates depend on density in design variable and objective space. New solution candidates are generated by stochastic variation but also systematically using a triangular grid. With respect to effective design analysis an approximation method is used. The proposed algorithm is evaluated using test cases and is successfully applied to dimension and shape optimization of a permanent magnet synchronous motor. ©2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.hybrid
Keywords: Cogging-torque reduction; Design optimization; Distributed analysis; Grid-based design generation; Hybrid algorithm; Multi-objective optimization; Objective value approximation; Permanent magnet motor

Identification of Differential Inductances of Permanent Magnet Synchronous Machines Using Test Current Signal Injection - Piepenbreier, Bernhard; et al. (SPEEDAM 2012, 2012)
In this paper a new kind of identification method for differential self and mutual inductances of permanent magnet synchronous machines (PMSMs) is proposed. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.identi_1
Keywords: cross-saturation; differential inductances; high frequency current injection method; permanent magnet synchronous machines; proportional-resonant current control

Identification of high frequency resistances and inductances for sensorless control of PMSM - Ebersberger, Sebastian; Seilmeier, Markus; Piepenbreier, Bernhard (IEEE International Symposium on Sensorless Control for Electrical Drives and Predictive Control of Electrical Drives & Power Electronics (SLED-PRECEDE 2013), 2013)
Recently published papers show that also a saliency in the high frequency (HF) resistances can be used for sensorless control. Those papers assume a diagonal HF resistance matrix. The aim of this paper is to show, based on experimental results, that a phenomenon like cross-saturation for the inductances is also existent for the HF resistances. The voltage drops caused by the HF resistances are typically very small and thus their identification is challenging. Therefore a high precision 3-phase current measurement is used and the dead-time and voltage drop errors caused by the inverter are compensated for. A high frequency test current control allowing zero steady-state control error is needed to overcome the limitations of voltage injection based methods. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.identi

Identification of high frequency resistances and inductances for sensorless control of PMSM - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (2013)
Recently published papers show that also a saliency in the high frequency (HF) resistances can be used for sensorless control. Those papers assume a diagonal HF resistance matrix. The aim of this paper is to show, based on experimental results, that a phenomenon like cross-saturation for the inductances is also existent for the HF resistances. The voltage drops caused by the HF resistances are typically very small and thus their identification is challenging. Therefore a high precision 3-phase current measurement is used and the dead-time and voltage drop errors caused by the inverter are compensated for. A high frequency test current control allowing zero steady-state control error is needed to overcome the limitations of voltage injection based methods.

Identification of Ohmic Stator Resistance Based on Low Frequency Current Signal Injection in Permanent Magnet Synchronous Machines - Kellner, Sven; Piepenbreier, Bernhard (EPE-PEMC 2010, 2010)
This paper introduces a novel approach to identifying the ohmic stator resistance Rs of permanent magnet synchronous machines (PMSM) based on low frequency signal injection. The identification does not depend on specific speed or load conditions. Besides the value of Lq(id, i q), no further electrical parameter is needed for the identification algorithm. The proposed stator resistance identification method is verified by two test benches. One contains an internal permanent magnet synchronous machine (IPMSM) the other a PMSM with surface-mounted permanent magnets. Each test bench has a dc machine as load. The IPMSM especially shows extensive harmonic effects. So an adequate filtering approach for the measured input values of the proposed identification algorithm is presented. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.identi
Keywords: Adjustable speed drive; Control of drive; Drive electrical drive; Electrical machine; Permanent magnet motor variable speed drive

Identification of steady-state inductances of PMSM using polynomial representations of the flux surfaces - Seilmeier, Markus; Piepenbreier, Bernhard (2013)
Sophisticated model based control strategies for permanent magnet synchronous machines (PMSM) require precise modeling and knowledge of the machine parameters to achieve a high performance drive control. Nonlinear material characteristics of the iron and permanent magnets used in the machine lead to time-variant modeling approaches to deal with those phenomena. Typically iron losses are not considered in control plant modeling. However, it has already been shown that iron losses and non-ideal characteristics of the power electronic converter can be a major source of deterioration for the steady-state PMSM parameter identification. In this paper an elegant two-step identification strategy is proposed which minimizes the impact of iron losses and compensates for the influence of converter voltage errors during the identification of the flux surfaces (first step). In the second step the steady-state inductances are identified using polynomial representations of the flux surfaces. Like this, in contrast to conventional methods, the inductances can be identified even for zero current.
Keywords: AC Machines; Inductances; Machine Vector Control; Magnetic Losses; Permanent Magnet Machines; Inductances; System Identification; Variable Speed Drives

Identification of steady-state inductances of PMSM using polynomial representations of the flux surfaces - Seilmeier, Markus; Piepenbreier, Bernhard (39th Annual Conference of the IEEE Industrial Electronics Society, 2013)
Sophisticated model based control strategies for permanent magnet synchronous machines (PMSM) require precise modeling and knowledge of the machine parameters to achieve a high performance drive control. Nonlinear material characteristics of the iron and permanent magnets used in the machine lead to time-variant modeling approaches to deal with those phenomena. Typically iron losses are not considered in control plant modeling. However, it has already been shown that iron losses and non-ideal characteristics of the power electronic converter can be a major source of deterioration for the steady-state PMSM parameter identification. In this paper an elegant two-step identification strategy is proposed which minimizes the impact of iron losses and compensates for the influence of converter voltage errors during the identification of the flux surfaces (first step). In the second step the steady-state inductances are identified using polynomial representations of the flux surfaces. Like this, in contrast to conventional methods, the inductances can be identified even for zero current. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.identi_5
Keywords: AC Machines; Inductances; Machine Vector Control; Magnetic Losses; Permanent Magnet Machines; System Identification; Variable Speed Drives

Identification of time-variant high frequency parameters for sensorless control of PMSM using an internal model principle based high frequency current control - Seilmeier, Markus; Böhm, Andreas; Hahn, Ingo; Piepenbreier, Bernhard (2012)
Standstill and low speed self-sensing based field oriented control of PMSM using the high frequency signal injection method requires a sufficient saliency ratio of the high frequency differential inductances of the machine. Therefore these inductances need to be known precisely to be able to guarantee stability of the sensorless control. In order to perform the identification, the conventional field oriented control scheme is extended by additional PI-type controllers in a positive and negative sequence high frequency coordinate system, thus resulting in zero steady state control error in case of superimposed sinusoidal high frequency test current reference values. Moreover the extended control scheme provides a direct demodulation of sine and cosine parts of the high frequency control signals and therefore enables a direct identification of all model parameters relevant for HF injection based sensorless control (differential self-and mutual inductances and high frequency resistances). In contrast to conventional methods, no prerequisites for the parameters or its' dependencies have to be fulfilled.
Keywords: nonlinear coordinate transformation; differential inductances; field-oriented control; internal model principle; parameter identification; PMSM; sensorless control; test current control

Identification of time-variant high frequency parameters for sensorless control of PMSM using an internal model principle based high frequency currrent control - Böhm, Andreas; Seilmeier, Markus; Hahn, Ingo; Piepenbreier, Bernhard (20th International Conference on Electrical Machines, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.identi

Impact of current measurement on switching characterization of GaN transistors - Lautner, Jennifer; Piepenbreier, Bernhard (Wide Bandgap Power Devices and Applications (WiPDA), 2014)
Gallium nitride (GaN) power devices promise better performance and efficiency compared to silicon transistors. How-ever, the switching characterization of GaN devices is challenging, because of the high switching speed. In this paper the switching behavior of a GaN transistor is investigated with special focus on the impact of current measurement. A circuit simulation model including the critical parasitic elements was built to analyze parasitic effects and their impact on the switching transients. To confirm the simulation results by experiments, a PCB board was designed and different current measurement methods are compared. It is shown that the current sensor adds additional inductance in the power loop and causes ringing and oscillations. Furthermore, it can be seen, that the current sensor resistance damps the oscillations and improves the switching transients. Therefor, both variables should be small in order to reproduce the real switching characteristics as accurate as possible.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.impact_2

Impact of Iron Losses and Parameter errors and back-EMF based sensorless control of PMSM - Seilmeier, Markus; Piepenbreier, Bernhard (IECON 2014, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.impact

Impact of Iron Losses and Parameter Errors on Back-EMF based Sensorless Control of PMSM - Seilmeier, Markus; Piepenbreier, Bernhard (2014)
Sensorless control of PMSM for mid and high speed range is typically based on back-EMF evaluation. Magnetic saturation has to be considered to achieve good position estimation results. To do so the flux versus current characteristic has to be stored in a look-up table or approximated by easy mathematical functions in the sensorless drive controller. The PMSM models typically used for back-EMF based sensorless control do not consider the impact of iron losses. Iron losses, however, cause steady state position estimation errors which increase in value with the rotational speed of the machine. In this paper the impact of iron losses and parameter errors is investigated. By including the iron losses in the PMSM model an identification strategy can be found which makes it possible to calculate the expected iron loss related errors for sensorless operation. Comparison of the position estimation errors calculated from the identified parameters show good accordance with position estimation errors obtained from measurements in sensorless control operation, if the machine temperature is approximately the same. But it was found that the error is significantly temperature dependent.
Keywords: permanent magnet motors; sensorless control; magnetic saturation; iron losses; parameter estimation

Impact of Iron Losses on Parameter Indentification of Permanent Magnet Synchronous Machines - Piepenbreier, Bernhard; Seilmeier, Markus; et al. (EDPC 2011, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.impact

Impact of Three-Phase Current Measurement on Field-Oriented Control - Piepenbreier, Bernhard; et al. (Power Conversion Intelligent Motion (PCIM), 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.impact

Initial Start-up and Magnet Polarity Estimation Method for HF Test Current Injection Based Sensorless Control of PMSM - Seilmeier, Markus; Piepenbreier, Bernhard (PEMC 2014, 2014)
This paper presents an initial start-up and magnet polarity estimation method for PMSM using the alternating HF test current injection based sensorless control scheme for low speed range and evaluation of the saturation dependent HF d-axis inductance. The proposed magnet polarity estimation method consists of two steps: The first step is to activate the HF injection based sensorless current control scheme providing either the orientation of the d or -d-axis. To eliminate the ambiguity of the result from the first step, the magnet polarity information is obtained in the second step by exciting the estimated d-axis with a DC current. The magnet polarity can be detected by evaluation of whether the d-axis inductance increases or decreases due to saturation. Initial position estimation errors which can occur due to secondary saliencies can be compensated for easily by use of the flatness based test signal pre-control which is used for the test current injection based sensorless control anyway. Experimental results show proper functioning of the proposed method.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.initia
Keywords: Current injection; Initial rotor position; Magnet polarity estimation; Permanent magnet motors; Saliency; Sensorless control

Initial start-up and magnet polarity estimation method for HF test current injection based sensorless control of PMSM - Seilmeier, Markus; Piepenbreier, Bernhard (2014)
This paper presents an initial start-up and magnet polarity estimation method for PMSM using the alternating HF test current injection based sensorless control scheme for low speed range and evaluation of the saturation dependent HF d-axis inductance. The proposed magnet polarity estimation method consists of two steps: The first step is to activate the HF injection based sensorless current control scheme providing either the orientation of the d or -d-axis. To eliminate the ambiguity of the result from the first step, the magnet polarity information is obtained in the second step by exciting the estimated (d) over cap -axis with a DC current. The magnet polarity can be detected by evaluation of whether the (d) over cap -axis inductance increases or decreases due to saturation. Initial position estimation errors which can occur due to secondary saliencies can be compensated for easily by use of the flatness based test signal pre-control which is used for the test current injection based sensorless control anyway. Experimental results show proper functioning of the proposed method.
Keywords: permanent magnet motors; magnet polarity estimation; initial rotor position; sensorless control; saliency; current injection

Lagegeberlose Positionsregelung eines permanenterregten Synchronlinearmotors - Ebersberger, Sebastian; Piepenbreier, Bernhard (at - Automatisierungstechnik, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.lagege_5

Measurement of Stator Resistance and Winding Temperature of Permanent Magnet Synchronous Machines without External Sensors - Kellner, Sven; Piepenbreier, Bernhard (VDE Kongress 2010, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.measur

Medium Frequency Transformer for Railway Application using New Materials - Hoffmann, Holger; Piepenbreier, Bernhard (EDPC 2011, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.medium_9

Model Based Closed Loop Control Scheme for Compensation of Harmonic Currents in PM-Synchronous Machines - Seilmeier, Markus; Arenz, Stefan; Piepenbreier, Bernhard; Hahn, Ingo (SPEEDAM 2010, 2010)
With increasing use of concentrated windings in permanent magnet synchronous machines harmonic effects have to be considered more and more for current control design. A structural expansion of the control scheme is needed to handle these higher harmonics. In this paper an effective method is proposed to carry out an expansion of the control scheme. Firstly the nonlinear disturbances are transformed into new fictitious rotating coordinate systems to get an easier description of the disturbances. The compensation of the harmonics is achieved in the new coordinates by applying closed loop controllers with suitable disturbance models. Therefore the control scheme is robust concerning parameter variations. In order to decouple reference and disturbance response a nonlinear model based dynamic feed forward control is used. The proposed control scheme is proven by test bench measurements. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.modelb
Keywords: Compensation of harmonics; Current oscillations; Permanent magnet synchronous machines; Two-degrees of freedom control scheme

Model Based Voltage Calculation for Inverters with small DC-Link Capacitance - Piepenbreier, Bernhard; von Zimmermann, Moritz; et al. (EDPC 2011, 2011)
Employing only a small capacitance in the DC-link of an adjustable speed drive (ASD) enables the replacement of electrolytic capacitors with film capacitors. Unfortunately, in combination with a diode bridge rectifier the DC-link voltage exhibits a significant six-pulse ripple. By measuring the DC-link voltage and providing the load side control with its value as widely done, this ripple can be compensated. In the following, a method is presented calculating the varying DC-link voltage by referring exclusively to the transfer function of the rectifier. This way, the DC-link voltage sensor can be omitted. Additionally, a partially damped mains filter is implemented to reduce line current oscillations. Experimental results verify the suitability of both the filter design and the model-based control. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.modelb
Keywords: capacitors; harmonic distortion; line filter; model-based control; small DC-link capacitance; variable speed drives; voltage source inverter (VSI)

Modeling of PMSM with Multiple Saliencies Using a Stator-Oriented Magnetic Circuit Approach - Seilmeier, Markus; Piepenbreier, Bernhard (International Electric Machines and Drives Conference 2011 (IEMDC 2011), 2011)
Precise modeling of PMSM needs considering the nonlinear characteristics of the hard and soft magnetic materials used in the machine. Therefore nonlinear machine models with time-variant parameters are used. Usually saturation is modeled in the field oriented coordinates assuming that the d-axis flux affects the q-axis flux and vice versa. If certain conditions are fulfilled cross saturation inductances can occur. This paper introduces a new modeling approach to consider multiple geometric and saturation induced saliencies based on a stator-oriented magnetic circuit approach. The advantage of this method is that all kind of saliencies that occur in the electrical machine can be considered simultaneously. Moreover modeling in the stator coordinates leads to a physically motivated explanation when the cross saturation effect can occur in a PMSM. The result of the new modeling approach are new insights for the interpretation of the resulting inductances in the field oriented model. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.modeli

Modeling of Wound Rotor Synchronous Machines considering Harmonics, Geometric Saliencies and Saturation induced Saliencies - Rambetius, Alexander; Luthardt, Sven; Piepenbreier, Bernhard (International Power Electronics Conference - ECCE Asia, 2014)
Advanced control techniques for wound rotor synchronous machines need precise machine models. Often a simple fundamental wave model is used to design the control algorithms. Using such a model, it is not possible to account for non-ideal effects that distort the control algorithm. Therefore a general machine model is derived by extending classical winding function theory. This analytical machine model considers higher harmonics as well as geometric saliencies and saturation induced secondary saliencies and leads to new insights for wound rotor synchronous machines. Firstly it is shown that, under certain conditions, the stator slots induce higher harmonics in the rotor winding. Moreover cross saturation effects are described. Last but not least the machine model provides information about the origin of certain harmonics and about their phase depending on saturation. The suggested machine model is verified experimentally by measurement results. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.modeli
Keywords: EESM; harmonics; saturation; synchronous motor; winding function theory; wound rotor synchronous machine

Modelling and Model Based Compensation of Non-Ideal Characteristics of Two-Level Voltage Source Inverters for Drive Control Application - Seilmeier, Markus; Wolz, Christoph; Piepenbreier, Bernhard (EDPC 2011, 2011)
In order to be able to optimize the performance of sophisticated model based AC machine control, precise models of the overall drive system are needed. This way compensation schemes for non-ideal characteristics can be derived based on the model inversion technique. Power electronic converters show the following non-ideal effects which have to be considered: turn-on delay time of the gate drive to prevent dc-link short-circuiting, non-ideal switching characteristics and forward voltages of the power electronic devices. In this paper models for these disturbances are derived and the respective compensation schemes are deduced. In constrast to conventional approaches for converter linearization, an analytic compensation law which allows considering different forward voltage-current characteristics of the diode and transistor is proposed. The effectiveness of this method is proven by means of experimental results. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.modell_0
Keywords: compensation of voltage errors; forward voltage drop; inverter nonlinearity; model inversion technique; non-ideal switching characteristic; VSI modelling

Multiple model based fault localization for HVDC transmission systems: Robustness and real-world performance - Al Hage Ali, Ali; Piepenbreier, Bernhard; Buchstaller, Dominic; Engel, Markus (2016 IEEE/PES Transmission and Distribution Conference and Exposition, T and D 2016, 2016)
This paper discusses the robustness properties of a novel, model-based HVDC fault localization algorithm. The approach utilizes a bank of Kalman filters to rank the fit of a discrete set of line fault models to measured data. The best fitting model indicates the fault position and fault type. The robustness of the algorithm in the presence of disturbances and unmodeled dynamics is demonstrated using synthetic data from high fidelity simulations as well as field data from a real HVDC transmission system.
Keywords: fault localization; HVDC protection; Kalman filter; multi-terminal; multiple model

Neutral Point Balancing for Three-Level Neutral Point Clamped Inverters Under Light Load Conditions - Lange, Alexander; Zimmermann, Marco; Piepenbreier, Bernhard (2018 21st International Conference on Electrical Machines and Systems (ICEMS), 2018)
Keywords: Inverters; Capacitors; Modulation; Current measurement; Topology; Switches; Voltage measurement; Multilevel converters; Three-Level Neutral Point Clamped inverter; Neutral Point Balancing; Light Load Conditions

Operating Strategy and Iron Loss Model of a Permanent Magnet Assisted Synchronous Reluctance Machine with a Ribless Rotor - Zimmermann, Marco; Schupp, Lino; Piepenbreier, Bernhard (2018 21st International Conference on Electrical Machines and Systems (ICEMS), 2018)
Keywords: Iron; Torque; Current measurement; Loss measurement; Rotors; Perpendicular magnetic anisotropy; Synchronous Reluctance Machine; Ferrite assisted; Operating strategy; Iron losses

PMSM d,q-Reference Frame Model using Absolute and Differential Inductance Surfaces - Ebersberger, Sebastian; Kellner, Sven; Piepenbreier, Bernhard (Power Conversion Intelligent Motion (PCIM), 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.pmsmdq

PMSM Model for Sensorless Control Considering Saturation Induced Secondary Saliencies - Ebersberger, Sebastian; Seilmeier, Markus; Piepenbreier, Bernhard (IEEE International Symposium on Sensorless Control for Electrical Drives and Predictive Control of Electrical Drives & Power Electronics (SLED-PRECEDE 2013), 2013)
Saliencies in electric machines are caused by the machine geometry and saturation. PMSM typically do not just show a single sinusoidal saliency, which is the main saliency utilized for position tracking. Secondary saliencies are a major source of deterioration for sensorless control, whereby saturation is reported to be the main problem. Cross-saturation, caused by a movement of the main flux away from the d-axis, results in steady-state position estimation errors. Moreover saturation can result in 6n-harmonic components in the inductances in field oriented coordinates. This effect causes position dependent estimation errors. Both effects need to be compensated for, if significant. For model based compensation a machine model with time-variant parameters is needed to cope with nonlinear material characteristics. A general machine model in field oriented coordinates considering multiple saliencies is derived and a method for systematic determination of the position dependent inductances is proposed. The machine model is verified by test bench measurement results. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.pmsmmo

PMSM Model for Sensorless Control Considering Saturation Induced Secondary Saliencies - Seilmeier, Markus; Ebersberger, Sebastian; Piepenbreier, Bernhard (2013)
Saliencies in electric machines are caused by the machine geometry and saturation. PMSM typically do not just show a single sinusoidal saliency, which is the main saliency utilized for position tracking. Secondary saliencies are a major source of deterioration for sensorless control, whereby saturation is reported to be the main problem. Cross-saturation, caused by a movement of the main flux away from the d-axis, results in steady-state position estimation errors. Moreover saturation can result in 6n-harmonic components in the inductances in field oriented coordinates. This effect causes position dependent estimation errors. Both effects need to be compensated for, if significant. For model based compensation a machine model with time-variant parameters is needed to cope with nonlinear material characteristics. A general machine model in field oriented coordinates considering multiple saliencies is derived and a method for systematic determination of the position dependent inductances is proposed. The machine model is verified by test bench measurement results.

Position-sensorless control of direct drive permanent magnet synchronous motors for railway traction - Frenzke, Thorsten; Piepenbreier, Bernhard (IEEE PESC 04, 2004)
A procedure for position-sensorless control of permanent magnet synchronous motors with surface mounted magnets is proposed, that is suitable to large traction drives with their restrictions like high inverter-utilisation and low switching frequency. Position and speed are obtained by an observer using a voltage and an inductance motor model together with test signal injection at low speed. Improvements of the basic estimation scheme are presented. The method has been tested successfully in the lab with a 28 kW standard servomotor.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEEAS.positi

P+Resonant Control of a Z-Source Inverter for Mains Voltage Drop Compensation - Piepenbreier, Bernhard; von Zimmermann, Moritz; et al. (EPE-ECCE 2011 - Birmingham, 2011)
Z-Source inverters, consisting of both inductors and capacitors as DC-link components, provide unique boost capability in contrast to conventional inverters. The simple structure needs no additional switching elements and only small step-up chokes. Due to the oscillatory arrangement of both inductors and capacitors in the DC-link, voltages and currents exhibit a characteristical six-pulse ripple when using the Z-source inverter with an AC supply. The consequences are distortion of the output voltage and self-boosting due to unwanted shoot-through states and oscillating DC-link voltage due to mains voltage rectifying. An active rectifier topology in combination with a damped mains filter is proposed to prevent any unwanted shoot-through states. Besides, regenerating operation of the Z-source inverter with AC supply is enabled. Resting on this new structure with minimized passive components, a state space description is given. Subsequently, a simple and robust P+resonant closed loop control is designed to avoid load current harmonics caused by mains voltage rectifying. For each frequency component of the six-pulse ripple, a separate controller is employed. The phase-shift of the Z-source network is compensated by additional all-pass filters. Experimental results verify the suitability. © 2011 EPE Association - European Power Electr.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.preson
Keywords: AC/AC converter; Adjustable speed driven; Converter controls; Emerging topology; Harmonics

Properties and Advantages of the Quasi-Z-Source Inverter for DC-AC-Conversion for Electric Vehicle Application - Beer, Eva Katharina; Piepenbreier, Bernhard (VDE Kongress 2010, 2010)
This paper presents features and advantages of the DC-AC quasi-Z-source inverter (qZSI) for use in electric vehicles. The qZSI with continuous input current and its wide range boosting ability is suitable for this application where a three-phase induction motor should be supplied from a lower battery voltage. At first, the theoretical circuit analysis will be given and on this basis dimensioning equations for the components are derived and verification is carried out by means of simulation. Lastly, experimental results and measurements made with a qZSI test setup will be given.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.proper
Keywords: Converter circuit; DC-AC power conversion; Inverters; Voltage-fed inverter; Z-source

Reduction of Torque and Radial Force Fluctuation in Permanent Magnet Synchronous Motors by Means of Multi-Objective Optimization - Piepenbreier, Bernhard; Ley, Thomas; et al. (EDPC 2011, 2011)
This work relates to external rotor type permanent magnet synchronous machines having surface mounted permanent magnets and two-layer non-overlapping windings. A short review of approaches to reduce fluctuation of forces presented in literature is given. As the reduction is associated in most cases with a negative influence on other important design goals, multi-objective optimizations are applied in conjunction with the finite element analysis yielding PARETO-optimal solutions with different preferences. PARETO-optimal solutions regarding the permanent magnet magnetization distribution and the current profiles minimizing the torque fluctuation of a 12-slot 8-pole machine and the higher frequency radial force harmonics in a 12-slot 10-pole machine are presented and discussed. A discrete PARETO-optimal magnetization distribution has been identified which promises a higher fundamental PM flux linkage amplitude compared to radial magnetization, but at a significantly lower cogging torque and torque ripple utilizing the balancing of open circuit voltage harmonics. Furthermore, it is shown that individual current harmonics affect individual radial force harmonics dominantly. A test setup is proposed and the numerically obtained instantaneous torque and the influence of current harmonics on the radial force amplitudes are verified with good agreement. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.reduct
Keywords: Acoustic noise; electromagnetic forces; pareto optimization; permanent magnet motors; variable speed drives; vibration measurement

Regenerating Operation of the Z-Source Inverter - von Zimmermann, Moritz; Sack, Lothar; Piepenbreier, Bernhard (Power Conversion Intelligent Motion (PCIM), 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.regene

Regenerative Drive Converter with Line-Frequency Switched Rectifier and without DC Link Components - Sack, Lothar; Piepenbreier, Bernhard (IEEE PESC 04, 2004)
The presented regenerative drive converter consists of a line-side three-phase rectifier and a motor-side three-phase inverter. Antiparallel to the rectifier diodes there are six IGBTs, which conduct the DC link current, if it flows from the inverter to the rectifier. In the DC link there are no components: neither an inductor or an electrolytic capacitor nor a braking resistor or a braking chopper. Between the line and the rectifier there is a filter, comprising a three-phase inductor and three capacitors. As the antiparallel IGBTs are switched with line frequency, their switching pattern is very simple, because it is synchronized with the line voltage. Because of the low additional effort this converter type is very advantageous, when regenerative operation is expected and when low frequency harmonic content of the line current is not critical and does not require a converter with pulsed active front end. The proposed paper describes the basic function of this type of converter. It is shown, that the simple switching pattern for the line-side IGBTs can be generated very easily. The requirements for the line-side filter, its topology and its design are illustrated. A test set-up of this converter with an induction-motor of 7.5 kW is described and experimental results hereof are presented. The DC-link voltage is not ideal, but superimposed by the line-harmonics caused by the rectifier. The resulting influences for the motor can be minimized by means of the PWM strategy of the motor-side inverter. The experimental results show, that the waveforms and the spectrum of the motor voltages and currents and the waveforms and the spectrum of the line currents confirm the theoretical considerations. Measurements of the efficiency of the rectifier show, that its losses are low because of the absence of switching losses. The experimental results show as well, that additional losses of the motor due to the fluctuating DC link voltage are negligible.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEEAS.regene

Regenerative SiC frequency converter with compact Z-source DC-link and sinusoidal output voltage - Lechler, Martin; Piepenbreier, Bernhard (SPEEDAM, 2012)
In this paper a new Z-source frequency converter with silicon carbide (SiC) components is presented. Both, the motor side and the line side converter, contain SiC-VJFETs using the reverse-conducting capability for freewheeling. The application of SiC transistors with their low switching losses, allows high switching frequencies (up to 125 kHz), so the volume of the DC-link and filter components is reduced. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.LEEAS.regene
Keywords: AC/AC converter; Gate Drive Unit; Silicon Carbide (SiC) VJFET; Z-Source topology

Rückspeisefähiger SiC-Stromrichter mit kompakten Filtern - Orellana Raccoursier, Alvaro Marcelo; Piepenbreier, Bernhard (Internationaler ETG-Kongress 2007, 2007)
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.LEEAS.rckspe

Sensorless Control of PMSM for base speed range using Two-Degree-of-Freedom MTPA current control and HF test current injection for low speed range - Seilmeier, Markus; Piepenbreier, Bernhard (2014)
In this paper a recently published innovative sensorless Two-Degree-of-Freedom current control scheme for the whole speed range is extended for a maximum torque per ampere (MTPA) control. Saturation is taken into account for the calculation of the MTPA trajectory by use of current dependent machine parameters which were identified beforehand. For low and zero speed operation test current injection is used to gain a position error signal. Sensorless control performance is deteriorated by cross-saturation and higher harmonic saliencies which are considered by current and position dependent inductances. A flatness based test signal pre-control provides compensation for those secondary saliencies. For mid and high speed operation the model based dynamic feed forward control is modified in order to achieve a high quality position error signal from the tracking controller. Like this no additional model based estimator evaluating back-EMF information is needed. The proper functioning of the proposed method is proven by experimental results.
Keywords: permanent magnet motors; sensorless control; maximum torque per ampere (MTPA); magnetic saturation; saliency; test current injection; Two-Degree-of-Freedom control

Sensorless Control of PMSM for the Whole Speed Range using Two-Degree-of-Freedom Current Control and HF Test Current Injection for Low-Speed Range - Piepenbreier, Bernhard; Ebersberger, Sebastian; Seilmeier, Markus (IEEE Transactions on Power Electronics, 2015)
In this paper, an innovative sensorless two-degree-of-freedom current control scheme for the whole speed range is proposed. It consists of a model-based dynamic feedforward control to set the reference response and model reference tracking controllers providing disturbance rejection and the position error signals needed for sensorless control. For low- and zero-speed operation, alternating test current injection is used to gain a position error signal. A flatness-based test signal precontrol provides compensation for secondary saliencies like cross-saturation and higher harmonics. For mid- and high-speed operation, it is shown how the model-based dynamic feedforward control can be modified to obtain a high-quality position error signal from the tracking controller. No additional model-based estimator evaluating back-EMF information is needed. The effectiveness of the proposed method is proven by experimental results.
UnivIS-Import:2015-07-08:Pub.2015.tech.IE.LEEAS.sensor_4
Keywords: Permanent magnet motors; saliency; sensorless control; test current injection

Sensorless Control of PMSM for the Whole Speed Range Using Two-Degree-of-Freedom Current Control and HF Test Current Injection for Low Speed Range - Seilmeier, Markus; Piepenbreier, Bernhard (International Power Electronics Conference - ECCE Asia (IPEC 2014), 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.sensor

Sensorless Control of PMSM for the Whole Speed Range Using Two-Degree-of-Freedom Current Control and HF Test Current Injection for Low-Speed Range - Seilmeier, Markus; Piepenbreier, Bernhard (IEEE Transactions on Power Electronics, 2015)
In this paper, an innovative sensorless two-degree-of-freedom current control scheme for the whole speed range is proposed. It consists of a model-based dynamic feedforward control to set the reference response and model reference tracking controllers providing disturbance rejection and the position error signals needed for sensorless control. For low-and zero-speed operation, alternating test current injection is used to gain a position error signal. A flatness-based test signal precontrol provides compensation for secondary saliencies like cross-saturation and higher harmonics. For mid-and high-speed operation, it is shown how the model-based dynamic feedforward control can be modified to obtain a high-quality position error signal from the tracking controller. No additional model-based estimator evaluating back-EMF information is needed. The effectiveness of the proposed method is proven by experimental results.
Keywords: Permanent magnet motors; saliency; sensorless control; test current injection

Sensorless Control of Short Stator Permanent Magnet Synchronous Linear Machines - A Renewed Approach International Conference and Exhibition for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management - Ebersberger, Sebastian; Piepenbreier, Bernhard (PCIM Europe, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.sensor_1

Sensorless control of SynRMs using an adaptive 2DoF current control including a comparison of two alternating HF signal injection-based methods - Bugsch, Martha; Held, Andreas; Piepenbreier, Bernhard (42nd Conference of the Industrial Electronics Society, IECON 2016, 2016)
Increasing interest in synchronous reluctance machines (SynRMs) shows the need to examine sensorless control methods for this machine type. For different speed ranges, different sensorless methods are necessary. The basic control structure used here is a cascaded field-oriented control (FOC) with a Two-Degree-of-Freedom (2DoF) current control with adaptive tracking controllers. This paper compares two alternating high-frequency (HF) test signal injection-based sensorless control methods for standstill and low speed. The first one superimposes an alternating HF test current signal and the second one an alternating HF test voltage signal onto the fundamental quantities in the estimated synchronous reference frame. To control the whole speed range, a method for the medium and upper speed range is necessary. Therefore, a back-EMF-based method is used. The implementation- and measurement-based differences for both alternating HF signal injection methods are analysed and the existing advantages and drawbacks are compared. Experimental results are included. They prove a similar behaviour of both alternating HF test signal-based sensorless control methods.
Keywords: HF test voltage injection; Sensorless control; Synchronous reluctance machines; 2DoF; Alternating test signal injection; HF test current injection

Sensorless Control of Wound Field Synchronous Machines for the whole Speed Range - Piepenbreier, Bernhard; Rambetius, Alexander (PCIM, 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.IE.LEEAS.sensor

Sensorless control of wound rotor synchronous machines using the switching of the rotor chopper as a carrier signal - Rambetius, Alexander; Piepenbreier, Bernhard (IEEE International Symposium on Sensorless Control for Electrical Drives and Predictive Control of Electrical Drives & Power Electronics (SLED-PRECEDE 2013), 2013)
Wound rotor synchronous machines open up new possibilities in carrier signal based sensorless control since the rotor voltage serves as an additional input to the system and the field current as an additional, easy to measure, state variable. Approaches for sensorless control of PMSMs use the stator as the transmitter and as the receiver of the carrier signal. A new alternative for wound rotor synchronous machines is to use the field winding as the transmitter and the stator as receiver. Since the field inductance is usually very large, a signal injection into the rotor is not reasonable because large rotor voltages are obligatory to create detectable stator currents. Therefore the presented approaches make use of the switching of the dc-field chopper as a carrier signal. Two methods are compared: The first method evaluates the stator currents in rotor fixed coordinates using a tracking observer. The second one uses the stator currents in stator fixed coordinates to directly compute the rotor position. Both methods consider cross saturation effects. In contrast to approaches for carrier signal based sensorless control of PMSMs no differential magnetic saliency is mandatory. Moreover no additional signal injection is necessary. Experimental results prove the performance of the proposed methods. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEEAS.sensor
Keywords: carrier signal injection; DC-excited synchronous machine; electrically excited synchronous machine; externally excited synchronous machine; sensorless control; synchronous motor; wound rotor synchronous machine

Space vector modulation for 3-Level Neutral Point Clamped inverters using predictive control methods for neutral point balancing - Lange, Alexander; Piepenbreier, Bernhard (2017 19th European Conference on Power Electronics and Applications (EPE'17 ECCE Europe), 2017)
Keywords: PWM invertors; predictive control; switching convertors; 3-level neutral point clamped inverters; FCS-MPC; finite control set model predictive control; neutral point balancing; predictive control methods; space vector modulation; switching sequence; Aerospace electronics; Europe; Inverters; Modulation; Predictive control; Switches; Field Programmable Gate Array (FPGA); Modelling; Modulation strategy; Multilevel converters; Optimal control; Pulse Width Modulation (PWM)

Space vector modulation for three-level simplified neutral point clamped (3L-SNPC) inverter - Lange, Alexander; Piepenbreier, Bernhard (18th IEEE Workshop on Control and Modeling for Power Electronics, COMPEL 2017, 2017)

Speed Estimation and Compensation for Harmonics in Sensorless Wound Rotor Synchronous Machines. - Rambetius, Alexander; Luthardt, Sven; Piepenbreier, Bernhard (IEEE International Symposium on Sensorless Control for Electrical Drives (SLED 2014), 2014)
The conventional approach to control synchronous machines without a motion sensor in medium and high speed range is model-based and evaluates the electromotive force (EMF). In this case the information about the rotor position is included in the fundamental wave of the EMF and therefore the presence of harmonics will distort the estimation result. In order to compensate for harmonics information about their frequency is a prerequisite. In the case of wound rotor synchronous machines it is possible to obtain an accurate estimate of the speed by tracking the effect of the stator slots in the rotor current. For the rotor winding the stator slots represent a position dependent reluctance variation and therefore the rotor current will contain a harmonic component which is related to the rotor speed. The frequency of this harmonic component is tracked using an adaptive tracking filter and is then used to compensate for harmonics in the stator currents. The compensation is done by using adaptive resonant controllers. The suggested approach is verified experimentally by a highly utilized machine which is designed for automotive traction applications and features an extra-low voltage DC-link. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.speede
Keywords: electrically excited synchronous machine; harmonics; sensorless control; stator slots; traction motors; wound field synchronous machine; Wound rotor synchronous machine

Steady-State Analysis of an AC-AC Z-Source Inverter including discontinuous Power Flow - von Zimmermann, Moritz; Piepenbreier, Bernhard (SPEEDAM 2010, 2010)
Z-Source inverters, consisting of both inductors and capacitors as DC link components, provide unique boost capability in contrast to conventional inverters. The simple structure needs no additional switching elements and only small step-up chokes. Due to the oscillatory arrangement of both inductors and capacitors in the DC link, voltages and currents exhibit characteristical dynamic behaviour especially if using the Z-source inverter with an AC supply. The consequences are discontinuous power flow and distortion of the output voltage. The authors derive analytic equations describing the steady-state behaviour of the Z-source inverter for all relevant variables with special regard to AC supply without additional high-performance measures, resulting in a discontinuous power flow. The significance of the approach is verified by practical tests. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.steady
Keywords: AC-AC converter; Dynamic analysis; Small-signal modeling; Z-source inverter

Test Signal based Speed Estimation for Induction Motor Drives - Piepenbreier, Bernhard; et al. (Epe Journal, 2010)
In the first part of the paper an estimation method for sensorless control employing a test signal based reference model is presented. The method estimates the slip frequency by a comparison of the measured test signal impedance curves while the machine is in operation with curves from a test signal based reference model. The reference model which describes the test signal behaviour of the machine is measured during DC magnetisation of a cold machine at steady state and constant rotor flux linkage. During normal machine operation the machine temperature and the stator frequency differ from these conditions and, thus, have a negative influence on quality of the estimation. In the second part of the paper the impact of these disturbances is investigated and two compensation strategies are presented. Measurements on two different standard induction machines which are not especially designed for sensorless control show that the estimation method allows safe operation at standstill and even at zero frequency.
UnivIS-Import:2015-03-09:Pub.2010.tech.IE.LEEAS.testsi
Keywords: Adjustable speed drives; Induction motor; Modelling; Sensorless drives

Umrichter mit netzfrequent geschaltetem Netzstromrichter - ein vorteilhaftes Konzept für integrierte Kompaktantriebe - Piepenbreier, Bernhard; Sack, Lothar (Elektrisch-mechanische Antriebssysteme, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEEAS.umrich_6

Utilisation of magnetic saliency for sensorless-control of permanent-magnet synchronous motors - Reill, Josef; Piepenbreier, Bernhard; Hahn, Ingo (SPEEDAM 2010, 2010)
This paper presents a new method for sensorless control of permanent magnet synchronous machines (PSM) in low speed and standstill region. Actually, there exist many solutions for speed controlled applications via interpretation of the voltage equations of the PSM. There are some well known algorithms to handle sensorless operation up to standstill, too. Most of these methods use a high frequency signal and some kind of filter technique for demodulation. In this paper a new frequency domain based algorithm is proposed. The main advantage of the new strategy is the precise separation of the fundamental wave and hf-signal and avoidance of conventional filters. For phaselag reasons all filter techniques suffer from the demand for high sampling rates. The presented algorithm is compared with known methods by far better applicable to conventional industry power-converters that often have switching frequencies limited to 8 kHz. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.LEEAS.utilis
Keywords: Sensorless control; Signal injection; Vector control

Verlustarmer Antriebsumrichter - rückspeisefähig mit geringem Aufwand - Kuskov, Andrey; Piepenbreier, Bernhard; Sack, Lothar (Internationaler ETG-Kongress 2007, 2007)
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.LEEAS.verlus

Verlustarmer Umrichter ohne Zwischenkreis-Kondensator - Piepenbreier, Bernhard; Sack, Lothar (Elektronik, 2006)
UnivIS-Import:2015-03-09:Pub.2006.tech.IE.LEEAS.verlus

Voltage square-wave-injection-based HF parameter identification method for sensorless control of a synchronous reluctance machine - Bugsch, Martha; Piepenbreier, Bernhard; Großmann, Dominik (19th European Conference on Power Electronics and Applications, EPE 2017 ECCE Europe, 2017)
For sensorless control at zero or low speed, extending the bandwidth by higher HF signal-injection frequencies is desirable. Therefore, knowledge of the HF machine parameters for the electrical angle calculation is necessary. Conventional methods to determine the HF machine parameters using sinusoidal signals reach their limits using a standard industrial converter. The restricted switching frequency limits the possible number of voltage steps for sinusoidal-shaped signals of higher frequencies. Moreover, the sampling frequency to reconstruct the current signal also is limited without current oversampling. An alternative and simultaneously simplified signal shape to avoid these limitations is a square-wave-shaped voltage signal. This kind of signal, in contrast to approximately sinusoidal-shaped signals, contains a different amount of higher harmonics if it is realised via pulse-width modulation. Thus, it is not recommended to use HF machine parameters that are measured with sinusoidal-signal injection even if the same frequency would be possible. Hence, a new method needs to be developed to measure the HF machine parameters for this signal shape and HF frequency under the restrictions of a standard industrial converter. This paper proposes a method to estimate the time-discrete transfer function between these square-wave-shaped voltage signal and the resulting current response with a least-square estimation method. A time synchronous averaging algorithm is implemented to reduce the measurement noise of the sampled current values. As a result, the HF admittances necessary for electrical angle estimation can be calculated. Measurement results are also presente
Keywords: "Self-sensing control"; "Eluctance drive"; "Synchronous motor"; "Sensorless control"

Z-Source-Antriebsumrichter - Eigenschaften und Potenzial für Industrieantriebe - - Sack, Lothar; von Zimmermann, Moritz; Piepenbreier, Bernhard (Elektrisch-mechanische Antriebssysteme, 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEEAS.zsourc_3

Z-Source Drive Inverter using modified SVPWM for low Output Voltage and regenerating Operation - Lechler, Martin; von Zimmermann, Moritz; Piepenbreier, Bernhard (EPE 2009 Barcelona, 2009)
Z-source inverters, consisting of both inductors and capacitors as DC-link components, provide unique boost capability with simple structure needing no additional switching elements. Due to complex operation modes of the Z-source inverter compared to a conventional inverter, boost operation, light load and regenerating operation cannot be achieved using common space-vector pulse width modulation. This paper proposes a modified SVPWM, derived from the known equations, to overcome this limitation. Besides, equations to control the output behaviour for all operating modes, such as buck, boost and regenerating operation, are given in detail. Finally, experimental results are presented.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEEAS.zsourc
Keywords: AC/AC converter; Adjustable speed drive; Drive; Emerging topology

Z-Source Inverter for General Purpose Drives in Motoring and Regenerating Operation - Sack, Lothar; Piepenbreier, Bernhard; von Zimmermann, Moritz (SPEEDAM 2008, 2008)
Due to rising energy costs and environmental aspects, high efficiency of electric drives is increasingly considered to be very important. Unfortunately, the efficiency of induction motors is very badly affected if terminal voltage is lowered. Unintentional undervoltage can be avoided regardless of its cause by means of the step-up effect of the Z-source inverter. The paper describes the selection of the components of the Z-source converter and a principle for operation with reduced stress to the components. The paper emphasizes the relevance of the output to input voltage ratio and of the DC link eigenfrequency for the installation size of the passive and active components. A presented design procedure for optimized throughput of power uses a DC equivalent circuit and leads to minimized passive components. With this set of parameters, further characteristics of electric and thermal stress of the components can be determined analytically and by simulation. The paper comprises design formulas in general form and their evaluation for an experimental test set-up for a 7.5 kW three-phase standard motor in motor and regenerative operation. ©2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEEAS.zsourc
Keywords: Drive; Regenerative braking; Z-sourced inverter